ANALYSIS OF DOLL PRODUCT QUALITY CONTROL USING STATISTICAL QUALITY CONTROL (SQC) METHODS AT PT AURORA WORLD CIANJUR - Santo Dewatmoko; Erika Nurmartiani; Muhamad Arief Ramdhany (Multifinance, 2025)
This study analyzed the doll quality control system at PT Aurora World Cianjur, which uses the Statistical Quality Control (SQC) method. Results show that tears (37.34%) and basting stitching (35.47%) are the two most dominant production defects, collectively accounting for 72.82% of all defects. Data were collected with check-sheets, while Pareto diagrams identified defect priorities, p-charts evaluated process stability, and fishbone diagrams diagnosed root causes. The most significant finding was that the production process became unstable in May, with the defect rate reaching 0.1536 well above the control limit. Operator skills, material quality, work methods, and environmental conditions were identified as the main contributing factors. Focused improvements are recommended: operator training, material standardization, SOP implementation, and work environment optimization. Consistently addressing these human, method, environment, and material factors is expected to significantly reduce defect rates and enhance export competitiveness.